Effective factors in dealing with industrial crises caused by widespread virus outbreaks - Adamian, MahdiReza; Toloie Eshlaghy, Abbas; Radfar, Reza; Pour Ebrahimi, Alireza (Social Determinants of Health, 2023)
Background: The global spread of the COVID-19 virus has not only posed a severe threat to public health but has also triggered a profound economic crisis affecting numerous industries. Addressing and mitigating the economic repercussions of the pandemic is imperative to prevent further damage. While prior research has explored the negative impacts of the COVID-19 pandemic on various industries, there has been a notable gap in understanding the specific factors that influence how industrial crises stemming from viral outbreaks are managed. Methods: This article undertakes a comprehensive investigation into these influential factors. Through in-depth interviews with industry experts, we identified a set of 30 pivotal variables in this context, forming the basis of an initial model. Subsequently, a questionnaire was administered to a cohort of one hundred managers and industry experts to assess these variables. Employing exploratory factor analysis, we categorized the 30 variables into six distinct categories: producer-related factors, supplier-related factors, distributor-related factors, retailer-related factors, consumer-related factors, and government-related factors. Results: Our findings revealed several strategic considerations for effectively addressing industrial crises in the face of viral outbreaks. These include the importance of building trust with customers in emerging markets, streamlining the adoption of digital technologies by customers, enhancing the customer relationship management process, prioritizing awareness, concern, and environmental consciousness, and providing support to consumers during times of viral spread. Conclusion: To effectively navigate industrial crises triggered by the widespread dissemination of viruses like COVID-19, businesses and governments should prioritize strategies that align with the identified factors. By focusing on these key areas, industries can bolster their resilience and minimize the adverse effects of such crises, ultimately contributing to economic stability and recovery in the face of global health emergencies.